2016
DOI: 10.1016/j.egja.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparing different fentanyl concentrations added to local anesthetic mixture in peribulbar block for cataract surgery

Abstract: Objective: Evaluation of the effect of different concentrations of fentanyl added to the local anesthetic mixture on the onset and duration of globe anesthesia, after peribulbar block, with the least side effects. Design: Double blinded randomized controlled clinical trial. Setting: Kasr Al Aini hospital, Cairo University. Methods: 60 patients with cataract grade 1-3 in the age group 40-70 years, with American Society of Anesthesiologists (ASA) grade I, II and III, scheduled for elective cataract surgery under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In concordance with our results, Kamel et al who evaluated the effect of addition of different doses of fentanyl to lidocaine in peribulbar block for cataract surgery and found that use of fentanyl as a local anesthetic additive in a concentration more than 2 μg/ml improve onset and duration of both sensory and motor block with improved patients satisfaction and postoperative analgesia without increasing incidence of side effects [15]. Also, Moustafa et al, who concluded that use of fentanyl 20 μg as an adjuvant to a mixture of mepivacaine and bupivacaine significantly prolong the duration of motor block and improve postoperative analgesia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In concordance with our results, Kamel et al who evaluated the effect of addition of different doses of fentanyl to lidocaine in peribulbar block for cataract surgery and found that use of fentanyl as a local anesthetic additive in a concentration more than 2 μg/ml improve onset and duration of both sensory and motor block with improved patients satisfaction and postoperative analgesia without increasing incidence of side effects [15]. Also, Moustafa et al, who concluded that use of fentanyl 20 μg as an adjuvant to a mixture of mepivacaine and bupivacaine significantly prolong the duration of motor block and improve postoperative analgesia.…”
Section: Discussionsupporting
confidence: 92%
“…Calculation of sample size based on results of a previous similar study [15] revealed that at least 26 patients in each group were required to detect a significant difference of the onset of globe akinesia of one minute at α value of 0.05 and 90% power of the study. The statistical analysis was done by the use of SPSS.…”
Section: Statistical Analysis Of Datamentioning
confidence: 99%
“…The addition of clonidine provided longer duration of peribulbar block as compared to fentanyl. On the other hand, Kamel et al [17] concluded that a concentration of P2-3 lg/ml of fentanyl didn't affect neither the onset nor the duration of both lid and globe akinesia when added to local anesthetics for peribulbar block in patients undergoing cataract surgery. They stated that this concentration only improved the quality of postoper- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the effect of adding different types of additives to improve the quality of block in ophthalmic local anesthesia with varying results [4][5][6][7][8] Adding neuromuscular blockers to the local anesthetic does not affect analgesia but induces akinesia in extraocular muscles which helps optimize the setting for ophthalmic surgery. The dose of rocuronium chosen in this study was less than one-tenth the dose administered intravenously for clinical neuromuscular blockade.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has the disadvantages of a slow onset of orbital akinesia [2] and the frequent need for block supplementation [3]. To overcome these limitations, many adjuvant drugs such as adrenaline, sodium bicarbonate, hyaluronidase, clonidine, and opioids [4][5][6][7][8] have been added to the local anesthetic mixture used for peribulbar block to augment its efficacy and hasten its speed of onset; however, their effects have been variable. Neuromuscular blocking drugs, such as vecuronium [9] and atracurium [10], have also been added to the local anesthetic mixture and have been shown to improve the quality of peribulbar anesthesia.…”
Section: Introductionmentioning
confidence: 99%